ACCEPTABILITY OF STEVIA AS NATURAL SWEETENER AND COCO CREAM AS STABILIZER FOR ICECREAM (Journal of Namibian Studies : History Politics Culture, 2022)
The main thrust of this study was to assess the acceptability of stevia as natural sweetener and coco cream as stabilizer for ice cream. Moreover, the utilization of stevia as natural sweetener and coco cream as stabilizer were tested in three different ice cream flavors namely: tableya, mango and avocado. This study employed the experimental design method through the aid of questionnaire using the 4-point Hedonic Scale conducted in Bohol Island State University-Main Campus. There were 100 respondents in the study. The respondents were students (70), faculty members or teaching staff (20) and support staff (10). The participants were selected through a purposive sampling. To determine the acceptability of the study, the data gathered were tabulated using the Weighted Mean to find out the respondents’ perception towards its acceptability. The findings revealed that all ice cream flavors which uses stevia as natural sweetener and coco cream as stabilizer were rated “Like Very Much” in all aspects. Hence, it was concluded that all ice cream flavors utilizing stevia and coco cream was accepted by the respondents in all aspects and has very promising potential in the market.It is recommended that ice cream products utilizing stevia as natural sweetener and coco cream as stabilizer be introduced in the university and put into income generation. Moreover, as part of the College of the Business and Management Extension program the study can be introduced to the Women’s Association in Upper Dela Paz Cortes Bohol.